Trauma-informed veterinary practice: linking emotional labor, moral distress, and occupational well-being - Serim-Yıldız, Begüm; Onaylı, Selin; Ilgın, Hüseyin Emre (Frontiers in Veterinary Science, 2026)
This study explores the emotional and psychological challenges inherent in veterinary practice, a profession situated at the intersection of empathy, ethics, and trauma. Despite its compassionate reputation, veterinary work frequently exposes practitioners to distressing experiences, including euthanasia, caregiver grief, and moral dilemmas, which can culminate in burnout and compassion fatigue. Drawing on a Trauma-Informed Care (TIC) perspective, this study explores veterinary professionals’ lived experiences and understands occupational distress as a systemic and relational experience rather than an individual shortcoming. By moving beyond individual-level burnout models, veterinary distress is reframed as an outcome of cumulative exposure to suffering, moral conflict, and emotionally charged caregiver interactions embedded within organizational contexts. Using a qualitative phenomenological design, semi-structured interviews were conducted with six veterinary professionals, with data collection concluding upon thematic sufficiency, identifying emotional stressors, coping mechanisms, and unmet psychoeducational needs. Findings reveal (1) persistent emotional exposure and moral conflict as key sources of stress, (2) limited institutional support and a prevailing culture of endurance, and (3) strong reliance on informal peer networks for emotional regulation. These findings underscore the need for trauma-informed education, structured debriefing, and peer support systems within veterinary institutions. For stakeholders, veterinary schools, professional associations, and clinics, adopting trauma-informed policies offers a practical route to mitigating compassion fatigue, enhancing psychological safety, and sustaining compassionate engagement in animal care.